The Russian economy : a very short introduction - Connolly, Richard, 1979- (Oxford : Oxford University Press, 2020)
For many, Russia's political influence far exceeds its weight in the global economy. Richard Connolly demonstrates that in fact Russia's economy affords it global power, and explores how its socialist past has shaped its economic system into a unique blend of state and market.
Also issued in print: 2020.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 30, 2020).
Keywords: Soviet Union -- Economic policy; Russia (Federation) -- Economic policy -- 1991-; Soviet Union -- Economic conditions; Russia (Federation) -- Economic conditions -- 1991-